Enhanced photoluminescence in CaMoO4:Eu3+ by Gd3+ co-doping - Singh B.P.; Parchur A.K.; Ningthoujam R.S.; Ansari A.A.; Singh P.; Rai S.B. (My University, 2025)
We have studied the luminescence property of CaMoO4:Eu3+. The emission peaks at 590 (5D0→7F1) and 613 nm (5D0→7F2) for Eu3+ are observed after excitation at 266 nm (i.e. Mo–O charge transfer band). The peak intensity of the latter dominates over the former indicating an asymmetric environment of Eu3+ in EuO8 polyhedron or parity mixing. Luminescence intensity increases significantly with co-doping of Gd3+. This is ascribed to energy transfer from Mo–O/Gd3+ to Eu3+. Luminescence intensity increases with annealing up to 900 °C due to the extent of decrease of non-radiative rates. Very high asymmetric values (A21) of 12–16 are found indicating a red emitter. As-prepared samples are dispersible in polar solvents like water, ethanol, methanol, dimethyl sulfoxide (DMSO) and ethylene glycol (EG); and among them, optimum luminescence is found in methanol. Polymer film shows red emission. The quantum yields of as-prepared 2 and 10 at% Gd3+ co-doped CaMoO4:Eu3+ under 277 nm (UV excitation) are 21 and 80%, respectively. © 2014 The Royal Society of Chemistry.